METODE MONTESSORI UNTUK MENGEMBANGKAN KARAKTER KEMANDIRIAN AUD DALAM PERSPEKTIF ISLAM - Nida Adilah; A. Yuri Alam F. (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2023)
The first 1000 days of a child's life is the golden age. In this period, various potentials develop in children. Among them, physical abilities, cognitive, affective, language, arts, social, emotional, moral, self-concept, independence, discipline, and religion. Independence and discipline are important parts of the concern of the Montessori method. In the Montessori method, adults provide full freedom and support for children's independence, through various types of activities. Children are allowed to observe and intervene in the types of daily activities, so that children will be more interested, responsible and concentrate on the tasks they are doing. So, in the end the child will achieve the character education process through the daily activities that have been carried out. In this study, we will briefly describe the combination of Islamic concepts and Montesori methods, especially for building character education, especially independence in children. The primary source in this study is the writings of Maria Montessori which have been translated into Indonesian entitled The Absorbent Mint "A Mind that Absorbs Easily", the Qur'an and Al Hadith. The results of the discussion in this paper are that it is hoped that parents can apply a number of things that help develop children's character education, such as: accustoming them to carrying out activities independently, teaching monotheism, telling what is haram and halal, instilling faith in Allah SWT, teaching worship , be honest, brave and always grateful as well as, be disciplined, but most importantly parents are expected to be a good whole example in every child's activity, because children are like sponges who easily absorb everything and imitate all behavior